New Smart Meter Policies Yielding Data (and Savings) for End‐Users. Issue 4 (November 2016) - Murray, Michael; Hawley, James
Abstract : The installation of smart meters in America was supposed to bring forth a plethora of energy management technologies that would engage both consumers and devices in the electricity system.